2020
DOI: 10.2147/idr.s263387
|View full text |Cite
|
Sign up to set email alerts
|

<p>Investigating the Effect of Nano-Curcumin on the Expression of Biofilm Regulatory Genes of <em>Pseudomonas aeruginosa</em></p>

Abstract: Background: Pseudomonas aeruginosa is an opportunistic pathogen that causes serious nosocomial infections, especially in immunodeficient patients and cystic fibrosis, cancer, and burned individuals. The biofilm that plays an important role in the virulence of P. aeruginosa is under the regulation of quorum sensing and two-component regulatory systems of bacteria. Curcumin, an active phenolic extract of turmeric has shown an inhibitory effect on the biofilm formation of some pathogenic bacteria. Thus, the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…The study indicated that a concentration of 25 µg/mL of nano-curcumin affirmatively inhibited the biofilm formation of P. aeruginosa strain ATCC 10,145. Further, nano-curcumin, prepared through Planetary Ball Mill technology, has more resistance to enzyme-induced hydrolysis, along with improved tissue solubility (Sharifian et al 2020). Spray-dried technology was used to co-administer curcumin-loaded PLGA nanoparticles and NAC to evaluate their co-effect in inhibiting infection in the pulmonary system.…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…The study indicated that a concentration of 25 µg/mL of nano-curcumin affirmatively inhibited the biofilm formation of P. aeruginosa strain ATCC 10,145. Further, nano-curcumin, prepared through Planetary Ball Mill technology, has more resistance to enzyme-induced hydrolysis, along with improved tissue solubility (Sharifian et al 2020). Spray-dried technology was used to co-administer curcumin-loaded PLGA nanoparticles and NAC to evaluate their co-effect in inhibiting infection in the pulmonary system.…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…Results showed that this nanoformulation increases the wound healing process by improving bioavailability, antioxidant and antiinflammatory activities, sustained drug release, and increased cell migration. In another study, Sharifian et al (2020). evaluated the antibacterial and antibiofilm activities of Cur nanoparticles in several concentrations (15, 20, and 25 μg/ml) against P. aeruginosa using the microplate titer method.…”
Section: Potential Therapeutic Applications Of Cur Nanoformulations I...mentioning
confidence: 99%
“…In a nutshell and precisely, it can be inferred that nanocurcumin/nanocomposites and curcumin exhibit efficient anti-P. aeruginosa and antibiofilm activity by inhibiting the QS system, retarding release of components for biofilm formation, biofilm disruption, ROS-mediated bacterial membrane, and ultrastructure damage. [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][71][72][73][74][75][76][77][78] Similarly, MRSA and MDR-S. aureus growth and biofilm can be effectively inhibited with nanocurcumin/nanocomposites and curcumin along with antibiotics, blue light-mediated PDI, cell penetrating peptide, and so on, that generate singlet oxygen and other ROS, thereby causing bacterial membrane damage and cytoplasmic leakage. Curcumin nanocomplex aerosols and crude curcumin (along with blue LED light-activated EDTA) have the potential to inhibit B. cepacia growth by mechanism that includes bacterial DNA and protein damage and intracellular content leakage.…”
Section: Mechanism Of Antibacterial Activity Of Curcumin Its Essentia...mentioning
confidence: 99%
“…In a nutshell and precisely, it can be inferred that nanocurcumin/nanocomposites and curcumin exhibit efficient anti‐ P. aeruginosa and antibiofilm activity by inhibiting the QS system, retarding release of components for biofilm formation, biofilm disruption, ROS‐mediated bacterial membrane, and ultrastructure damage 51–66,71–78 . Similarly, MRSA and MDR‐ S. aureus growth and biofilm can be effectively inhibited with nanocurcumin/nanocomposites and curcumin along with antibiotics, blue light‐mediated PDI, cell penetrating peptide, and so on, that generate singlet oxygen and other ROS, thereby causing bacterial membrane damage and cytoplasmic leakage 79–102 .…”
Section: Mechanism Of Antibacterial Activity Of Curcumin Its Essentia...mentioning
confidence: 99%